2008
DOI: 10.1128/mcb.01953-07
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Structure and Expression of a Gene Transcribed by RNA Polymerase III Are Independent of H2A.Z Deposition

Abstract: The genes transcribed by RNA polymerase III (Pol III) generally have intragenic promoter elements. One of them, the yeast U6 snRNA (SNR6) gene is activated in vitro by a positioned nucleosome between its intragenic box A and extragenic, downstream box B separated by ϳ200 bp. We demonstrate here that the in vivo chromatin structure of the gene region is characterized by the presence of an array of positioned nucleosomes, with only one of them in the 5 end of the gene having a regulatory role. A positioned nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 68 publications
3
51
0
Order By: Relevance
“…This profile of H2A.Z is similar to the general pattern of H2A.Z-containing nucleosomes flanking an NFR around the TSS, reported for active pol II-transcribed genes (10). However, IEL analysis shows that similar to SNR6 (17); the chromatin structure remains unperturbed in the absence of H2A.Z, even under repression (Figure 2D, lanes 7–10), supporting a previous report showing no role of H2A.Z in general nucleosome positioning or maintenance of nucleosomal organization (27). H2A.Z associates with both active and inactive genes (28).…”
Section: Resultssupporting
confidence: 85%
“…This profile of H2A.Z is similar to the general pattern of H2A.Z-containing nucleosomes flanking an NFR around the TSS, reported for active pol II-transcribed genes (10). However, IEL analysis shows that similar to SNR6 (17); the chromatin structure remains unperturbed in the absence of H2A.Z, even under repression (Figure 2D, lanes 7–10), supporting a previous report showing no role of H2A.Z in general nucleosome positioning or maintenance of nucleosomal organization (27). H2A.Z associates with both active and inactive genes (28).…”
Section: Resultssupporting
confidence: 85%
“…Similar NFR is seen on two other pol III-transcribed genes, RNA170 and ZOD1 (Figure 1C). We had earlier reported a similar arrangement on SNR6 with NFR spanning over its TATA box and A box regions [17]. Such a common scheme of arrangement on rest of the non-tRNA genes or any special arrangement with reference to upstream TATA box or introns found in some of tDNAs is not seen.…”
Section: Resultsmentioning
confidence: 88%
“…Presence of chromatin remodelers RSC and Isw2 on pol III-transcribed genes has also been reported [13,14]. RSC shows different remodeling activity on pol II and pol III-transcribed genes [15] and regulates pol III-transcribed SNR6 and SUP4 genes [16,17]. Recent studies with human pol III-transcribed genes have reported that the presence of pol II and pol II-specific chromatin marks near pol III-transcribed genes generates an active chromatin milieu for them [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…The Nhp6 proteins were originally implicated in pol III transcription through their positive effect on SNR6 gene transcription, which requires a positioned nucleosome for optimal expression from its atypically-spaced promoter elements [9699]. The Nhp6 proteins also affect pol III transcription from tRNA genes through their effect on TFIIIB positioning, specifically TBP binding, and the fidelity of transcription initiation [98,100102].…”
Section: Targets For Regulation Of Pol III Transcriptionmentioning
confidence: 99%